2014
DOI: 10.4238/2014.january.31.5
|View full text |Cite
|
Sign up to set email alerts
|

Specific BRCA1 gene variations amongst young Moroccan breast cancer patients

Abstract: ABSTRACT. Germline mutations in the BRCA1 gene are known predictive markers for the development of hereditary breast cancer. Nevertheless, no comprehensive study has been performed targeting the presence and relevance of BRCA1 mutations in Moroccan breast cancer patients. We here present an analysis of BRCA1 gene regions (exon 2 and exon 11a/b) of 50 female Moroccan breast cancer patients with early disease onset (≤40 years) or familial disease backgrounds. Results showed that no mutation was present in either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
(29 reference statements)
2
15
0
Order By: Relevance
“…Some studies found that this SNP is associated with patients under 40 years old, 66,67 , which agreed with our study -the youngest premenopausal patient (27 years old) was detected with this variant. Although this variant's effect remains uncertain, a previous finding to our study has described the same mutation, Q356R in Moroccan BC patients, which was the first study that described this mutation in a North African population 66 . They found that most previous studies that described this mutation were within western European populations 68 and there were no studies found in a North African population to confirm this, thus more research is needed to investigate this.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Some studies found that this SNP is associated with patients under 40 years old, 66,67 , which agreed with our study -the youngest premenopausal patient (27 years old) was detected with this variant. Although this variant's effect remains uncertain, a previous finding to our study has described the same mutation, Q356R in Moroccan BC patients, which was the first study that described this mutation in a North African population 66 . They found that most previous studies that described this mutation were within western European populations 68 and there were no studies found in a North African population to confirm this, thus more research is needed to investigate this.…”
Section: Discussionsupporting
confidence: 82%
“…The same protein position (Q356R) with the same altered nucleotide (A/G) has also been described previously, but with a different nucleotide position c.1186 A>G 16,65,66 . Some studies found that this SNP is associated with patients under 40 years old, 66,67 , which agreed with our study -the youngest premenopausal patient (27 years old) was detected with this variant.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The mutational spectrum of BRCA1/2 in the Moroccan population is becoming partially characterised thanks to local genetic centers, who have developed oncogenetic consultations for familial forms of breast and ovarian cancers and performed molecular analyses of BRCA genes using the conventional individual exon-by-exon Sanger sequencing (10,13,14,16,17). Thus, several mutations in two particular genes have been reported in the Moroccan National Genetic Database (http:// ethnos.findbase.org/home-ma).…”
Section: Discussionmentioning
confidence: 99%
“…research.nhgri.nih.gov/bic/), the HGMD (http://www.hgmd. cf.ac.uk/ac/index.php), Clinvar (http://www.ncbi.nlm.nih.gov/ clinvar/) and previous publications (10,(13)(14)(15). Amino acid predictions were performed using the scale-invariant feature transform algorithm and PolyPhen-2 software tools (Polymorphism Phenotyping v2.2.2, developed by Dr Shamil Sunyaev, Harvard Medical School, Boston, MA, USA; http://genetics.…”
Section: Template Preparation By Emulsion Polymerase Chain Reaction (mentioning
confidence: 99%